Public Perception of COVID-19 Booster Vaccination Qualitative Study in the Silangit Health Center Working Area North Tapanuli Regency in 2022 - Ruth Hardianty Hersana Naiborhu; Otniel Ketaren; Nettietalia Brahmana (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
The covid-19 pandemic is a large-scale epidemic that affects millions of people in various countries, sometimes spreading worldwide. The administration of the Covid-19 vaccine aims to reduce the transmission of the coronavirus, reduce morbidity and mortality, achieve herd immunity and protect the public from Covid-19. The study aimed to determine community perceptions of the covid-19 booster vaccination qualitative study in the Silangit Health Center Working Area, North Tapanuli Regency, in 2022. The type of research used is a qualitative approach. This research was conducted in the Silangit Health Center Working Area, North Tapanuli Regency, from December 2022 - January 2023. The research informants were ten people. Research instruments using interview guidelines, digital camera, data collection matrix, and notebook. The results of the study, Informants explained that the covid-19 virus is a virus that causes respiratory system disorders, is transmitted through coughing and sneezing and a virus that causes many fatalities or deaths. The informant explained that the signs and symptoms of covid-19 are high fever, cough, flu, sore throat, dizziness for several days, body weakness, loss of smell or taste, skin changes, respiratory problems, chest pain, decreased consciousness, and sore throat until death. Informants explained that booster vaccination prevents the covid-19 virus, acts as an antiviral, controls the body's immunity, strengthens antibodies, and maintains immunity. The informant's perception of the booster vaccine is that the informant does not want to be vaccinated because he is afraid of the side effects that occur due to the absence of definite information about the side effects of booster vaccination; the informant also answered that he felt lazy to be vaccinated because he considered it did not have much effect on the body. Keywords: Booster Vaccination, Covid-19, Virus